2019
DOI: 10.1128/mcb.00314-19
|View full text |Cite
|
Sign up to set email alerts
|

GATA2 and PU.1 Collaborate To Activate the Expression of the Mouse Ms4a2 Gene, Encoding FcεRIβ, through Distinct Mechanisms

Abstract: GATA factors GATA1 and GATA2 and ETS factor PU.1 are known to function antagonistically during hematopoietic development. In mouse mast cells, however, these factors are coexpressed and activate the expression of the Ms4a2 gene encoding the β chain of the high-affinity IgE receptor (FcεRI). The present study showed that these factors cooperatively regulate Ms4a2 gene expression through distinct mechanisms. Although GATA2 and PU.1 contributed almost equally to Ms4a2 gene expression, gene ablation experiments re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 63 publications
2
13
0
Order By: Relevance
“…PU.1 recruits the chromatin looping factor LDB1 to the Spi1 locus, which confers an active chromatin configuration and facilitates autoregulation ( Schuetzmann et al., 2018 ). We also reported that PU.1 bound to the Ms4a2 gene locus recruits LDB1, which promotes GATA binding and robust Ms4a2 expression ( Ohmori et al., 2019 ). Therefore, a similar mechanism may operate in the Il6 locus.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…PU.1 recruits the chromatin looping factor LDB1 to the Spi1 locus, which confers an active chromatin configuration and facilitates autoregulation ( Schuetzmann et al., 2018 ). We also reported that PU.1 bound to the Ms4a2 gene locus recruits LDB1, which promotes GATA binding and robust Ms4a2 expression ( Ohmori et al., 2019 ). Therefore, a similar mechanism may operate in the Il6 locus.…”
Section: Discussionmentioning
confidence: 93%
“…Motif analysis of the 646 GATA2 peaks showed enrichment of GATA transcription factors followed by ETS domain transcription factors and runt domain transcription factors (RUNX) ( Figure 1 C). Because the ETS family transcription factor PU.1 functions with GATA2 in mast cells in several contexts ( Ohmori et al., 2019 ; Baba et al., 2012 ), we delineated the genome-wide binding profile of PU.1 using ChIP-seq in the same LPS-treated and untreated BRC6 cell samples. We identified 25,258 PU.1-binding peaks that commonly arose in the untreated and LPS-treated cells ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ChIP analysis revealed a shared region between GATA2 and PU.1 at a +10.4 kbp region downstream of Ms4a2 gene locus that encodes for β chain of the high-affinity IgE receptor (FcεRI), while a −60 bp region exclusively occupied by GATA2. The study also elucidated that ablation of PU.1 interfered with the binding of GATA2 to both the regions ( 129 ). Thus, the coregulation of these TFs plays a central role in the modulating the expression of mast cell genes by binding to common regulatory regions.…”
Section: Transcription Factor Network In Mast Cellsmentioning
confidence: 90%
“…Although GATA2 governs early hematopoietic development, mature hematopoietic and numerous other cell lineages in adult tissues sustain GATA2 expression as well ( Harigae et al., 1998 ; Li et al., 2015 ; Ohmori et al., 2012 ; Tsai and Orkin, 1997 ; Watanabe-Asaka et al., 2020 ; Wilson et al., 1990 ; Yu et al., 2014 ; Zon et al., 1993 ). For example, our group and others have demonstrated that GATA2 plays a key role in the maintenance and function of mast cells and participates in allergic inflammatory responses ( Li et al., 2017 , 2021 ; Ohmori et al., 2015 , 2019 ; Ohneda et al., 2019 ). We also showed that GATA2 exacerbated inflammatory kidney injury by promoting cytokine production from renal collecting duct cells ( Yu et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%